82 The COL5A1 Gene and Risk of Achilles Tendon Pathology in a British Cohort. (5th September 2014) - Khoury, Louis El; Posthumus, Michael; Collins, Malcolm; Ribbans, William; Raleigh, Stuart
Abstract : Background: Achilles tendon pathologies (ATPs) such as Achilles tendinopathy and Achilles tendon ruptures have been identified as debilitating conditions resulting from either acute or repetitive overuse loading mechanisms. ATP is a multifactorial condition for which several genetic risk factors have been identified. Notably, the COL5A1 rs12722 genetic variant has been associated with risk of Achilles tendinopathy in South African and Australian populations. 1, 2 Further, the COL5A1 rs71746744, rs16399 and rs1134170 variants were also associated with Achilles tendinopathy within combined South African and Australian populations. 3 The rs71746744 within the 3'-UTR of the COL5A1 gene has been shown to be functional. 4 Objective: The objective if this study was to investigate if the COL5A1 rs12722 and rs71746744 variants are associated with ATP in a British (UK) cohort. Methods: One hundred and thirty six (52 females and 84 males) participants diagnosed with Achilles tendon pathology (ATP group) and 131 (49 females and 82 males) asymptomatic healthy controls (CON group), were recruited for this case-control genetic association study. ATP, which includes non-insertional and insertional Achilles tendinopathy, as well as Achilles tendon rupture were diagnosed using MRI scans and ultra-sound imaging. This study was approved by the Research Ethics committees of the University of Northampton and the University of Cape Town and all participants gave written informed consent. SNP genotyping was performed using a fluorescence-based custom-made TaqMan (rs71746744) and restriction fragment length polymorphism assays (rs12722) from DNA extracted from saliva samples. The significance of all statistical testing was accepted at p < 0.05. Results: No significant genotype frequency distributions were detected in the UK cohort between the CON and ATP groups for the rs12722 (p = 0.658) and rs71746744 (p = 0.319) variants. However, when only the male participants were investigated, the TT genotype of the rs12722 (p = 0.015) and the INS/INS (p = 0.031) of the rs71746744 variant was significantly over-represented within the ATP groups. Conclusion: This study showed that both COL5A 1 rs12722 and rs71746744 variants were significantly associated with risk of ATP within males. It is unknown why this association was not found in the female participants investigated. References: Mokone GG, et al . Scandinavian Journal of Medicine & Science in Sports. 16(1):19–26 September AV, et al . British Journal of Sports Medicine. 43(5):357–365 Abrahams Y, et al . Annals of Human Genetics. 77(3):204–214 Laguette N, et al . Matrix Biology. 30(5–6):338–345